Thorax support vest to prevent sternal wound infections in cardiac surgery patients—a systematic review and meta-analysis - Caldonazo, T; Dell’Aquila, M; Cancelli, G; Harik, L; Soletti, GJ; Fischer, J; Kirov, H; Rahouma, M; Ibrahim, M; Demetres, M; An, KR; Girardi, L; et al. (Oxford University Press, 2024)
OBJECTIVES: Midline sternotomy is the main surgical access for cardiac surgeries. The most prominent complication of sternotomy is sternal wound infection (SWI). The use of a thorax support vest (TSV) that limits thorax movement and ensures sternal stability has been suggested to prevent postoperative SWI. METHODS: We performed a meta-analysis to evaluate differences in clinical outcomes with and without the use of TSV after cardiac surgery in randomized trials. The primary outcome was deep SWI (DSWI). Secondary outcomes were superficial SWI, sternal wound dehiscence, and hospital length of stay (LOS). A trial sequential analysis was performed. Fixed (F) and random effects (R) models were calculated. RESULTS: A total of 4 studies (3820 patients) were included. Patients who wore the TSV had lower incidence of DSWI [odds ratio (OR) = F: 0.24, 95% confidence interval (CI), 0.13–0.43, P < 0.01; R: 0.24, 0.04–1.59, P = 0.08], sternal wound dehiscence (OR = F: 0.08, 95% CI, 0.02–0.27, P < 0.01; R: 0.10, 0.00–2.20, P = 0.08) and shorter hospital LOS (standardized mean difference = F: −0.30, −0.37 to −0.24, P < 0.01; R: −0.63, −1.29 to 0.02, P = 0.15). There was no difference regarding the incidence of superficial SWI (OR = F: 0.71, 95% CI, 0.34–1.47, P = 0.35; R: 0.64, 0.10, 4.26, P = 0.42). The trial sequential analysis, however, showed that the observed decrease in DSWI in the TSV arm cannot be considered conclusive based on the existing evidence. CONCLUSIONS: This meta-analysis suggests that the use of a TSV after cardiac surgery could potentially be associated with a reduction in sternal wound complications. However, despite the significant treatment effect in the available studies, the evidence is not solid enough to provide strong practice recommendations.